Significane of intravascular coagulation in canine endotoxin shock. - From, A H (1975)
The contribution of disseminated fibrin clot formation to the pathogenesis of canine endotoxin shock was explored in control dogs and in those defibrinated with a purified fraction of Malayan pit viper venom. The hemodynamic and humoral responses after the administration of an intravenous challenge dose of Escherichia coli endotoxin were comparable as was mortality. It is concluded that, although the role of the coagulation sequence in canine endotoxin shock is unclear, it does not appear to be determinative.